PENGARUH PEMBERIAN MADU TERHADAP KADAR KOLESTEROL TOTAL DAN TRIGLISERIDA TIKUS PUTIH ( Rattus norvegicus L.) JANTAN GALUR WISTAR YANG DIINDUKSI TUAK - DEA YULIA LUBIS; ROBITAH ASFUR; MEIZLY ANDINA; HUMAIRAH MEDINA LIZA LUBIS (LP2MTBM MAKARIOZ, 2019)
Metabolic syndrome is accumulation of symptoms that induce cardiovascular disease. Cardiovascular disease is the first cause of death and has a high prevalence in the world. According to the study in Finlandia, people with metabolic syndrome will have 3,5 higher risk of cardiovascular disease. In metabolic syndrome the level of triglyceride will increase because of atherogenic diet, less of physical activity, and alcohol consumption. Honey is a sweet liquid that is produced by the bee from nectar and contains antioxidant. Objective : This experiment study the effect of honey for total cholesterol and triglyceride in Wistar male white rat (Rattus norvegicus L) induced by tuak. Method : this was true experimental study with pretest-posttest with control group design. Result : Based on data in hypothesis test from Wilcoxon test and Mann-Whitney test, there were an effect of honey in mean of total cholesterol level and triglyceride that was showed by reduction of total cholesterol level and triglyceride with p<0,05.. Conclusion : there were an effect of honey in total cholesterol level and triglyceride from Wistar male white rat (Rattus norvegicus L) induced with tuak.